Differential modulation of IL-4, IL-10, IL-17, and IFN-γ production mediated by IgG from Human T-lymphotropic virus-1 (HTLV-1) infected patients on healthy peripheral T (CD4+, CD8+, and γδ) and B cells - Machado, Nicolle Rakanidis; Fagundes, Beatriz Oliveira; Fernandes, Lorena Abreu; Oliveira, Augusto César Penalva de; Nukui, Youko; Casseb, Jorge; Cunha, Fernando Roberto Machado; Nali, Luiz Henrique da Silva; Sanabani, Sabri Saeed; Victor, Jefferson Russo (Frontiers in Medicine, 2023)
Human T-lymphotropic virus 1 (HTLV-1) infected individuals remain as asymptomatic carriers (ACs) or can develop the chronic neurological disorder HTLV-1-associated myelopathy/Tropical Spastic Paraparesis (HAM/TSP) or the adult T-cell leukemia/lymphoma (ATLL), and the immunological mechanisms involved in this pathologies need to be elucidated. Recently, it has been demonstrated that induced or naturally developed IgG repertoires obtained from different groups of donors, grouped by immune status, can modulate human T and B cell functions. Here we aimed to evaluate if the IgG obtained from HTLV-1-infected ACs, HAM/TSP, and ATLL patients can differentially modulate the production of cytokines by human T and B cells. With this purpose, we cultured PBMCs with IgG purified from ACs, HAM/TSP, or ATLL donors and evaluated the frequency and intracellular cytokine production by flow cytometry. Our results indicate that IgG from HAM/TSP patients could induce an augment of IL-17-producing CD4+ T cells, reduce the frequency of IL-4-producing CD4+ T cells, increase IFN-γ-producing CD8+ T cells, and reduce IL-4-producing CD8+ T cells. IgG from ATLL could reduce the frequency of IL-4-producing CD4+ T cells, similarly to IgG from HAM/TSP /TSP, and could reduce the frequency of IFN-γ-producing γδT cells without influence on IL-17- and IL4-producing γδT and could reduce the frequency of IL-10- producing B cells. Finally, IgG from both HAM/TSP and ATLL patients could reduce the frequency of IFN-γ producing B cells. In conclusion, these results suggest that these preparations are active, partly overlapping in their effects, and able to elicit distinct effects on target populations.